Self-Esteem and Its Predictive Factors Among Women with Obstetric Fistula in Ethiopia: A Facility-Based Cross-Sectional Study - Bekana Hurissa; Zewdie Koricha; Lelisa Dadi (Mashhad University of Medical Sciences, 2022)
Background & aim: Women living with obstetric fistulas have been known to have increased depression, anxiety, and other mental health dysfunctions. Evidence shows that due to the obstetric fistula condition, there is a frequent maternal loss of self-esteem. Very few studies have identified sources of diminished self-esteem among women living with obstetric fistulas. Thus, this study aimed to assess self-esteem and its predictive factors among women with obstetric fistula in Ethiopia.Methods: A cross-sectional study was employed on consecutively selected 478 women in five fistula treatment centers in Ethiopia from April 01 to August 01, 2019. Data were collected using an interviewer-administered structured questionnaire and analyzed using SPSS 23 software. Simple and multiple linear regression models were fitted for data analysis.Results: The mean self-esteem score was 24.53 ± 4.79. Age (β =-0.05; 95% CI=-0.10, -0.002), educational status at primary school (β=1.08; 95% CI =0.07, 2.09), overall quality of life (β=0.19; 95% CI=0.09,0.29), satisfaction with health (β=0.26; 95% CI=0.16, 0.36), and knowledge of fistula risk factors (β=0.22; 95% CI=0.01, 0.43) were significant predictors of the self-esteem of women with obstetric fistula.Conclusion: The self-esteem of women with obstetric fistula was low. All concerned bodies dealing with obstetric fistula should emphasize on holistic care for women with obstetric fistulas, work on  their awareness, training and counseling in relation to the risk factors of fistulas, and should work in ways that enhance the overall quality of life and health satisfaction of women living with obstetric fistula, which could then improve their self-esteem.